Microcystin-LR increases genotoxicity induced by aflatoxin B1 through oxidative stress and DNA base excision repair genes in human hepatic cell lines. (February 2018) - Liu, Wenyi; Wang, Lingqiao; Zheng, Chuanfen; Liu, Lebin; Wang, Jia; Li, Daibo; Tan, Yao; Zhao, Xilong; He, Lixiong; Shu, Weiqun
Abstract: Aflatoxin B1 (AFB1) and microcystin-LR (MC-LR) simultaneously exist in polluted food and water in humid and warm areas, and each has been reported to be genotoxic to liver and associated with hepatocellular carcinoma (HCC). However, the genotoxic effects of the two biotoxins in combination and potential mechanism remain unknown. We treated the human hepatic cell line HL7702 with AFB1 and MC-LR together at different ratios, examined their genotoxic effects using micronuclei and comet assays, and evaluated the possible mechanism by measuring oxidative stress markers and DNA base excision repair (BER) genes. Our data show that co-exposure to AFB1 and MC-LR significantly increased DNA damage compared with AFB1 or MC-LR alone as measured by the levels of both micronuclei and tail DNA. Meanwhile, AFB1 and MC-LR co-exposure showed biphasic effects on ROS production, and a gradual trend towards increased Glutathione (GSH) levels and activity of Catalase (CAT) and Superoxide Dismutase (SOD). Furthermore, MC-LR, with or without AFB1, significantly down-regulated the expression of the base excision repair (BER) genes 8-oxoguanine glycosylase-1 (OGG1) and X-ray repair cross complementing group 1 (XRCC1). AFB1 and MC-LR in combination upregulated the expression of the BER gene apurinic/apyrimidinic endonuclease 1 (APE1), whereas either agent alone had no effect. In conclusion, our studies show that MC-LR exacerbates AFB1-induced genotoxicity and we report for the first time that this occurs through effects on oxidative stress and the deregulation of DNA base excision repair genes. Graphical abstract: Image 1 Highlights: AFB1 and MC-LR simultaneously exist in polluted food and water in tropical areas. AFB1 or MC-LR exposure alone is reported to be genotoxic to the liver. We found that the combination of AFB1 and MC-LR has increased genotoxicity in vitro . MC-LR and AFB1 co-exposure affects oxidative stress in vitro . MC-LR regulates DNA base excision repair genes to increase combinatorial genotoxicity.